Assessment of antibiotic storage practices, knowledge, and awareness related to antibiotic uses and antibiotic resistance among household members in post-conflict areas of Pakistan: Bi-central study - Khan, Faiz Ullah; Mallhi, Tauqeer Hussain; Khan, Qasim; Khan, Farman Ullah; Hayat, Khezar; Khan, Yusra Habib; Ahmad, Tawseef; Fang, Yu (Frontiers in Medicine, 2022)
Background: The storage of antimicrobials at homes is frequently practiced in various developing countries, which could result in irrational use, resistance, and toxicities. This condition may worsen more in conflicted regions where health facilities are limited. This study was aimed to determine the storage and use of leftover antibiotics among households (HHs) along with knowledge and awareness about antibiotics and antibiotic resistance (ABR). Methods: A descriptive cross sectional study design was employed. Members of the HHs were invited to participate in the survey while using a convenient sampling technique. The data were obtained using a validated questionnaire and analyzed through SPSS. Results: A total of 96 HHs were randomly selected from two districts (n=50, n=46), with most of the participants being men between the ages of 18 and 28 (n=45, 46.9%) years. The majority of HHs families (n=32, 33.3%) had 6-8 total members, with 1-2 chronic diseases (n=63, 65.6%), individual families (n=60, 62.5%), and with (n=35, 36.5%) LRTIs (lower respiratory tract infections). The HHs were aware of the word "antibiotic" (n=59, 61.5%) and gave correct replies to amoxicillin as an antibiotic (n=42, 43.8%), on the other hand, HHs have thought of paracetamol as an antibiotic (n=45, 47.9%). HHs were identified as the most common brands of antibiotics easily. The majority of HHs (n=69, 71.9%) had never heard of ABR before, and HHs had lower levels of awareness. The most stored antibiotic at homes (n=38, 39.6%) was azithromycin (J01FA10). In addition, the HHs had multiple needless 1-2 (n=62, 64.6%) and 3-4 (n=29, 30.2%) antibiotics in their houses. Conclusion: Education level, occupation, and age groups have a strong association (p<0.05) with the knowledge of the participants. Participants have stored various antibiotics of different classes in their homes. Lack of knowledge related to the appropriate usage of antibiotics, use of leftover antibiotics, and awareness related to ABR were unknown to the participants.